Analysis of key factors and equity in influenza vaccination among Chinese adults-evidence from a large national cross-sectional survey - Dong, Bo; Xu, Hengxuan; Tang, Ning; Jiang, Menghan; Lei, Zhihao; Han, Yue (Frontiers in Public Health, 2025)
IntroductionInfluenza is prevalent globally, leading to severe morbidity and mortality. Vaccination remains a critical strategy for influenza prevention. Although previous studies in China have primarily focused on influenza vaccination among children, limited research has addressed the key determinants and equity issues concerning adult influenza vaccination.The purpose of this study was to investigate the key factors influencing influenza vaccination and its equity among Chinese adults.MethodsThe study uses data from the 2021 Chinese General Social Survey (CGSS) (N = 2695).Initially, differences in influenza vaccination among adults with various baseline characteristics were analyzed using the chi-square test. Subsequently, the importance of influencing factors was assessed through a random forest model, with LASSO used for variable selection. Following this, weighted logistic regression analysis was applied to quantify the significant influencing factors. Finally, the concentration index was employed to identify and determine the contribution of important variables to influenza vaccination.ResultsThe influenza vaccination rate among Chinese adults is low (6.75%). Key factors identified as influencing adult vaccination include government trust, physician trust, income, aging concerns, health insurance, age, education, and health status. These factors not only have independent effects but also interact to influence vaccination behavior. Regarding individual effects, government trust, physician trust, income, and aging concerns showed positive associations with vaccination rates. Conversely, health insurance status, age, educational attainment, and health status demonstrated negative associations. Regarding the interaction terms, there were positive associations between health insurance and government trust, education and government trust, health and physician trust, government trust, as well as education level and age with the target variables. In contrast, interactions between income and health insurance, as well as income and physician trust negatively influenced vaccination rates. The concentration index for adult influenza vaccination was 0.092. There was inequity in vaccination, with the distribution of vaccinations being skewed toward higher-income individuals. Decomposition analysis further revealed that the primary contributors to vaccination inequity, in descending order of magnitude, were income (32.6%), government trust (9.1%), education (8.7%), age (8.2%), and aging concerns (2.6%).DiscussionThis is the first study to leverage a large micro-survey database in China to analyze the key factors affecting adult influenza vaccination and its equity. By providing new evidence on influenza vaccination among Chinese adults, the findings may inform the optimization of adult immunization policies. To further increase influenza vaccination rates and promote equity among Chinese adults, future policy improvements could consider emphasizing the role of trust in vaccination uptake, subsidizing vaccination costs, and fully utilizing comprehensive intervention strategies to enhance adult influenza vaccination coverage and equity.